Efeitos da microgravidade em plantas de cana-de-açúcar - Silva, Helaine Cristiane (2013)
Sugarcane (Saccharum spp.) is a plant from Poaceae family that has an impressive ability to accumulate sucrose in the stalk, making it a significant component of the economy of many countries. About 100 countries produce sugarcane in an area of 22 million hectares worldwide. For this reason, many studies have been done using sugarcane as a plant model in order to improve production. A change in gravity may be one kind of abiotic stress, since it generates rapid responses after stimulation. In this work we decided to investigate the possible morphophysiological, biochemical and molecular changes resulting from microgravity. Here, we present the contributions of an experiment where sugarcane plants were submitted to microgravity flight using a vehicle VSB-30, a sounding rocket developed by Aeronautics and Space Institute teams, in cooperation with the German Space Agency. Sugarcane plants with 10 days older were submitted to a period of six minutes of microgravity using the VSB-30 rocket. The morphophysiological analyses of roots and leaves showed that plants submitted to the flight showed changes in the conduction tissues, irregular pattern of arrangement of vascular bundles and thickening of the cell walls, among other anatomical changes that indicate that the morphology of the plants was substantially influenced by gravitational stimulation, besides the accumulation of hydrogen peroxide, an important signaling molecule in stress conditions. We carried out RNA extraction and sequencing using Illumina platform. Plants subjected to microgravity also showed changes in enzyme activity. It was observed an increased in superoxide dismutase activity in leaves and a decreased in its activity in roots as well as for ascorbate peroxidase activity. Thus, it was concluded that the changes in gravity were perceived by plants, and that microgravity environment triggered changes associated with a reactive oxygen specie signaling process. This work has helped the understanding of how the gravity affects the structural organization of the plants, by comparing the anatomy of plants subjected to microgravity and plants grown in 1g gravity